2016
DOI: 10.1021/acs.biomac.6b00366
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Thermosensitive Hydrogel for Cartilage Bioprinting and Its Biofunctionalization with Polysaccharides

Abstract: Hydrogels based on triblock copolymers of polyethylene glycol and partially methacrylated poly[N-(2-hydroxypropyl) methacrylamide mono/dilactate] make up an attractive class of biomaterials because of their biodegradability, cytocompatibility, and tunable thermoresponsive and mechanical properties. If these properties are fine-tuned, the hydrogels can be three-dimensionally bioprinted, to generate, for instance, constructs for cartilage repair. This study investigated whether hydrogels based on the polymer men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 74 publications
6
97
0
Order By: Relevance
“…To visualize the orientation of the collagen fibers, other sections were stained with picrosirius red (1 μg/ml, 60 min) with Weigert's hematoxylin as counterstain. Collagen types I, II, and VI were visualized with immunohistochemistry as previously described (Abbadessa et al, 2016). The stained sections were scanned with a NanoZoomer-XR Digital slide scanner (C12000-02, Hamamatsu, Almere, The Netherlands) while the picrosirius stained sections were evaluated with a light microscope and a polarizing filter (BX51 with a DP70 camera, Olympus, Hamburg, Germany).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…To visualize the orientation of the collagen fibers, other sections were stained with picrosirius red (1 μg/ml, 60 min) with Weigert's hematoxylin as counterstain. Collagen types I, II, and VI were visualized with immunohistochemistry as previously described (Abbadessa et al, 2016). The stained sections were scanned with a NanoZoomer-XR Digital slide scanner (C12000-02, Hamamatsu, Almere, The Netherlands) while the picrosirius stained sections were evaluated with a light microscope and a polarizing filter (BX51 with a DP70 camera, Olympus, Hamburg, Germany).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…HAMA was analyzed by 1 in which an integration value of 1 is given to the signal at chemical shift of 6.2 ppm. The DM of HAMA was also measured according to a High Performance Liquid Chromatography (HPLC)-based method, as reported previously [24,42].…”
Section: Synthesis and Characterization Of Polymersmentioning
confidence: 99%
“…Our more recent studies have shown that by blending these PEG/methacrylated pHPMAlac triblock copolymers with UV cross-linkable polysaccharides, i.e. methacrylated chondroitin sulfate [23] or methacrylated hyaluronic acid [24], hydrogels with improved mechanical characteristics and degradation profiles can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OC plugs were embedded in paraffin and tissue sections (5 µm) were cut for the visualization of matrix components (Abbadessa et al, 2016). Safranin-O/Fast green staining was performed to visualize collagens (green/blue) and GAGs (red) (Wall and Board, 2014).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%